WAYS OF ENSURING EFFECTIVE USE OF LOCAL BUDGET FUNDS (Scientific journal of the Fergana State University, 2023)
This article elucidates the issues of ensuring effective usage of local budget in the example of Ferghana region and presents scientifically-practical substantiations, suggestions and conclusions on their bases.